Choques econômicos durante a gravidez, peer effects e a iniciação do hábito de fumar entre adolescentes no Brasil: evidências a partir da pesquisa nacional de saúde do escolar 2012 - Cunha Júnior, José Maria da (2015)
Using as a database the PeNSE (2012), this research intends to investigate the determinants of smoking initiation among adolescents in Brazil using a duration model (Cox proportional hazard models) through a population study (over 100,000 observations) regarding students characteristics. The proposed model confronts variables capturing the students smoking habit, their socioeconomic and demographic characteristics, parental characteristics and their smoking habit, the school's environment and exogenous shocks during pregnancy on the risk of adolescents initiate the experience with cigarette. Estimates found in this study show the relationship between exogenous shocks during pregnancy and the likelihood that the child try cigarette. For instance, while unemployment rate fluctuations during pregnancy potentiated the risk of the adolescent starts smoking, the increase in the tobacco inputs price reduced that risk. This result highlights the fact that the risk of initiation into smoking can be traced even during the gestational phase. That is, we showed the initial effects (early life effects) importance. Another result worth mentioning is the existence of peer effects (smokers parents and students) on adolescent decision to start smoking. Regarding the parents, it was verified a positive relationship in the influence of smoking parents in the child's decision to start smoking. Also, the likelihood of smoking initiation is influenced positively by students of the same class who have already had experience with cigarette. Some variables were inhibiting on smoking initiation probability, for example the possible parent negative reaction if aware about the son's smoking habit and the fact that living with parents also reduced the probability of initiation. In summary, we belive this study contributes to the literature regarding the determinants of smoking initiation, something crucial for public policies design preventing and combating smoking.